Guillem de la Tor, "En vos ai mesa" (BdT 236.3a); An., "Finamens" (BdT 461.122) - Paolo Canettieri (Lecturae Tropatorum, 2014)
For more than a century discussion has taken place as to the relationship between the descort and the lai, two forms that reveal clear structural affinities to the point that Jeanroy published all the Old French poems belonging to both genres in a single volume. Nevertheless some scholars have suggested a possible polygenesis, also considering the greater structural freedom displayed by the lai compared to the more rigid structure of the descort, which is more typical of troubadour and courtly poetry. The relationship between the two texts examined here is that of a contrafactum, though it is hard to say which inspired the other: a comparison between them points out the distinguishing features of the two genres and in some instances enables some problematic lessons in both texts to be resolved.